Unveiling The Importance of Plastic Waste Education for Children in Islamic Religion - Aura Fajria Putri, Keisha (Gunung Djati Conference Series, 2025)
Plastic waste around us has been increasing year by year, yet public awareness of its harmful impacts remains relatively low. Environmental damage caused by plastic is already evident across oceans, land, and even the air. Education about plastic waste is important, especially for children, considering that they are the future generation who will inherit today's environmental impact. In this context, environmental education using an Islamic perspective is interesting to study because it combines spiritual values, ethics, and moral responsibility with sustainable practices, thereby providing a more holistic approach to shaping environmentally friendly behavior. However, research on plastic education remains limited, particularly from the perspective of educating children through the lens of Islamic studies. In response to this gap, this study aims to explore research trends related to plastic waste education for children within the framework of Islamic discourse. The study employs a qualitative approach through bibliometric analysis using VOSviewer. Data were collected from the Scopus database, comprising 83 publications from 2015 to 2025, using the keywords “plastic” and “waste education”. The findings are expected to map and visualize trends in publication years, authors, and emerging keywords. By identifying these trends, the study seeks to offer recommendations on how to effectively educate children to adopt more environmentally friendly lifestyles, grounded in current research developments. These findings are particularly important in addressing environmental challenges through a more theoretical and analytical approach to keyword mapping. The results of this study explain that children can also become solutions or key actors for existing problems as individuals who have a more environmentally friendly and sustainable lifestyle as in the guideline of Islam